From Silos to Synergy: Conceptualizing an integrated infrastructure design for climate resilience in Rotterdam - Angela Ordóñez Llancce; Yirang Lim; Theresa Audrey O. Esteban; Joep van Leeuwen; Johan Ninan (Climate Risk Management)
In recent years, municipalities have been recognised for their crucial role in protecting cities from climate change impacts by adopting mitigative and adaptive strategies to enhance climate resilience. However, anchoring these strategies demands multiple interventions, which are often hindered by the current siloed organization of departments and disciplines. An integrated infrastructure design approach (IIDA) can co-create a process that converges sectors, disciplines, and actors’ interests to tackle this challenge. To this end, this research explores how municipalities can effectively implement IIDA to enhance climate-resilient infrastructures. The city of Rotterdam served as a case study involving a thematic analysis of 21 interviews with internal actors of the municipality. This study identified 19 key factors influencing a municipality’s effectiveness in using an integrated design approach to enhance climate resilience. These influential factors belong to six different dimensions: Human Capacity, Organisational Culture, Governance, Communication, Project Development Process and Finance. The findings suggest that it is essential that actors within municipalities have soft skills such as proactivity and open-mindedness for collaboration. Furthermore, it is necessary to foster an innovative and collaborative culture to enable the development of pilot projects. This, in turn, helps update standards and scale up implementation by aligning integration at the three management levels: strategic, program, and project. Based on the findings, we recommend establishing a multi-dimensional baseline, setting up a communication strategy and tools, build human and institutional capacity through pilots and living labs. This can help municipalities implement an integrated infrastructure design in their organisation, offering a promising future in designing climate-resilient infrastructures.